Pengaruh Pengetahuan Awak Kapal, Pengawasan dan Fasilitas Pengelolaan Sampah terhadap Kinerja Awak Kapal Melalui Mitigasi Pencegahan Pencemaran Laut di Pelabuhan Tanjung Priok - Erika Dwi Setyorini; Djuliyanto Djuliyanto; Bambang Sumali; Erwin F. Manurung; Marihot Simanjuntak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of ship crew knowledge, supervision, and waste management facilities on ship crew performance by mitigating the prevention of marine pollution at Tanjung Priok Port. This research uses a quantitative approach with an explanatory research design and Structural Equation Modeling (SEM) techniques to analyze the data obtained. Primary data was collected through questionnaires distributed to 100 crew members from 10 ships operating at Tanjung Priok Port. The analysis results show that the knowledge of ship crews has a positive and significant effect on their performance, which is mediated by mitigation efforts to prevent marine pollution. Strict supervision of ship operations also has a considerable positive impact on improving crew performance. In addition, adequate waste management facilities are proven to play an important role in supporting the performance of ship crews through the mitigation and prevention of marine pollution. In conclusion, the influence of ship crew knowledge, supervision, and waste management facilities on ship crew performance through mitigating the prevention of marine pollution at Tanjung Priok Port. Keywords: Ship Crew Knowledge, Supervision, Waste Management Facilities, Ship Crew Performance, Prevention of Marine Pollution